Post-infectious vasculitis secondary to Campylobacter coli infection. (May 2023) - Collercandy, Nived; Ramdani, Yanis; Audemard-Verger, Alexandra; Legot, Floriane; Maillot, François; Ferreira-Maldent, Nicole
HIGHLIGHTS: Vascular inflammation may be linked to Campylobacter coli infection. Post-infectious vasculitis may cause relapsing fever after an acute infection. 18F-fluorodeoxyglucose positron emission tomography/computed tomography may be helpful for the diagnosis of post-infectious vasculitis.